Enantioselective Nickel‐Catalyzed Hydrocyanation of Homostilbenes. Issue 10 (13th February 2023) - Strache, Joss Pepe; Münzer, Lukas; Adler, Andreas; Blunk, Dirk; Schmalz, Hans‐Günther
Abstract: We investigated the previously unknown enantioselective Ni‐catalyzed hydrocyanation of 1, 3‐diarylpropenes (homostilbenes). For this purpose, a series of ( E )‐homostilbenes were prepared by (microwave‐assisted) Pd‐catalyzed coupling of allylic alcohols with aryl‐boronic acids. Employing our established catalyst system formed from Ni(cod)2 and a TADDOL‐derived chiral phosphine‐phosphite ligand and using TMSCN as an in situ source of HCN, the hydrocyanation of various homostilbenes was studied. The synthetic usefulness of the methodology was demonstrated in a short synthesis of the new (allo‐) colchicine analogue 7‐cyano‐11‐methoxy‐colchinol involving an PIDA‐mediated oxidative cyclization of the corresponding hydrocyanation product to set up the 7‐membered ring. The absolute configuration of 2, 4‐diphenylbutyronitrile was assigned by comparison of experimental and calculated ECD spectra. Abstract : Despite the danger of "chain walking", the asymmetric nickel‐catalyzed hydrocyanation of ( E )‐1, 3‐diarylpropenes, which are readily accessible by microwave‐assisted Pd‐catalyzed coupling of allylic alcohols with arylboronic acids, proceeds with useful levels of regio‐retention and enantioselectivities of up to 88.12 e.r. This opens a particular short access to novel colchicinoids.